2010
DOI: 10.1111/j.1365-2966.2010.17560.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen enrichment in atmospheres of A- and F-type supergiants

Abstract: Using new accurate fundamental parameters of 30 Galactic A and F supergiants, namely their effective temperatures T eff and surface gravities log g, we implemented a non-LTE analysis of the nitrogen abundance in their atmospheres. It is shown that the non-LTE corrections to the N abundances increase with T eff . The nitrogen overabundance as a general feature of this type of stars is confirmed. A majority of the stars have a nitrogen excess [N/Fe] between 0.2 and 0.9 dex with the maximum position of the star's… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 44 publications
7
42
0
Order By: Relevance
“…These values are in good agreement with those found by Aufdenberg et al (2008) for the primary star, (24750 ± 500, 3.71 ± 0.06). For the secondary, our result is in agreement with Aufdenberg et al's log g pole = 4.16 ± 0.05, and Lyubimkov et al (1995) T pole eff = 20800 ± 1500 K.…”
Section: The Impact Of Interaction Effects On T Eff and Log Gsupporting
confidence: 82%
“…These values are in good agreement with those found by Aufdenberg et al (2008) for the primary star, (24750 ± 500, 3.71 ± 0.06). For the secondary, our result is in agreement with Aufdenberg et al's log g pole = 4.16 ± 0.05, and Lyubimkov et al (1995) T pole eff = 20800 ± 1500 K.…”
Section: The Impact Of Interaction Effects On T Eff and Log Gsupporting
confidence: 82%
“…The [C/Fe] and [N/Fe] ratios are +0.1 and +0.3, respectively, while the C/O ratio is 0.55. The [N/Fe] ratio is a bit high but could be overestimated by up to 0.2-0.3 dex due to non-LTE effects (Lyubimkov et al 2011). The [C/Fe] and C/O ratios are significantly larger than the typical ratios of −0.31 and 0.25, respectively, found in Cepheids.…”
Section: Lithium and V1033 Cygmentioning
confidence: 89%
“…Non-LTE effects in CNO have been considered by Fabbian et al (2006) for carbon, by Lyubimkov et al (2011) for nitrogen, and by Takeda & Takada-Hidai (1998) In the temperature range 5800-6400 K, Lyubimkov et al (2011) give the non-LTE correction for N i as + 0.2 to + 0.3 dex in the sense that LTE abundances are larger. Our gf values for N i 744.2 and 746.8 nm are about 0.2 dex higher than assumed by Lyubimkov et al This means our LTE values would be at −0.2 dex relative to theirs, thus when the non-LTE correction is added our nitrogen abundances should be on the same scale as theirs.…”
Section: Possible Non-lte Effectsmentioning
confidence: 99%
“…Lyubimkov et al (2011) observed such nitrogen enhancements in A-and F-type supergiants which could have obtained their nitrogen enrichment from rotational mixing during a B-type MS lifetime. To examine this further it would have been useful to investigate the relationship between observed nitrogen enrichment and fundamental parameters such as the mass and main sequence lifetime of our objects.…”
Section: Nitrogen Abundancesmentioning
confidence: 95%